Endotoxin levels and contribution factors of endotoxins in resident, school, and office environments — A review. (October 2016) - Salonen, Heidi; Duchaine, Caroline; Létourneau, Valérie; Mazaheri, Mandana; Laitinen, Sirpa; Clifford, Sam; Mikkola, Raimo; Lappalainen, Sanna; Reijula, Kari; Morawska, Lidia
Abstract: As endotoxin exposure has known effects on human health, it is important to know the generally existing levels of endotoxins as well as their contributing factors. This work reviews current knowledge on the endotoxin loads in settled floor dust, concentrations of endotoxins in indoor air, and different environmental factors potentially affecting endotoxin levels. The literature review consists of peer-reviewed manuscripts located using Google and PubMed, with search terms based on individual words and combinations. References from relevant articles have also been searched. Analysis of the data showed that in residential, school, and office environments, the mean endotoxin loads in settled floor dust varied between 660 and 107, 000 EU/m 2, 2180 and 48, 000 EU/m 2, and 2700 and 12, 890 EU/m 2, respectively. Correspondingly, the mean endotoxin concentrations in indoor air varied between 0.04 and 1610 EU/m 3 in residences, and 0.07 and 9.30 EU/m 3 in schools and offices. There is strong scientific evidence indicating that age of houses (or housing unit year category), cleaning, farm or rural living, flooring materials (the presence of carpets), number of occupants, the presence of dogs or cats indoors, and relative humidity affect endotoxin loads in settled floor dust. The presence of pets (especially dogs) was extremely strongly associated with endotoxin concentrations in indoor air. However, as reviewed articles show inconsistency, additional studies on these and other possible predicting factors are needed. Highlights: Mean endotoxin loads in settled floor dust were 660–107, 000 EU/m 2 . Mean airborne endotoxin concentrations in indoor air were 0.04–1610 EU/m 3 . There were several strong determinants for the endotoxin loads. The presence of pets was extremely strong determinant for the endotoxin concentration. Literature findings concerning several determinants were inconsistent.